2009
DOI: 10.4049/jimmunol.0713269
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Polyclonal Mouse Antithymocyte Globulin Administration Alters Dendritic Cell Profile and Function in NOD Mice to Suppress Diabetogenic Responses

Abstract: Mouse antithymocyte globulin (mATG) prevents, as well as reverses, type 1 diabetes in NOD mice, through mechanisms involving modulation of the immunoregulatory activities of T lymphocytes. Dendritic cells (DC) play a pivotal role in the generation of T cell responses, including those relevant to the autoreactive T cells enabling type 1 diabetes. As Abs against DC are likely generated during production of mATG, we examined the impact of this preparation on the phenotype and function of DC to elucidate novel mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This observation is consistent with the known negative impact of GVHD and/or its treatment on B-lymphopoiesis (4447). There also appears to be a GVHD-independent effect of ATG (Supplementary Figure 3) which we hypothesize is related to the known positive effect of ATG on Th2 cells (48). For memory/effector CD8 T cells, the reason is not clear.…”
Section: Discussionmentioning
confidence: 86%
“…This observation is consistent with the known negative impact of GVHD and/or its treatment on B-lymphopoiesis (4447). There also appears to be a GVHD-independent effect of ATG (Supplementary Figure 3) which we hypothesize is related to the known positive effect of ATG on Th2 cells (48). For memory/effector CD8 T cells, the reason is not clear.…”
Section: Discussionmentioning
confidence: 86%
“…It may also influence the interaction between T cells and endothelial cells through modulating expression of adhesion molecules [22]. Our recent study showed that ATG therapy eliminated certain subset of dendritric cells and induced tolerogenic dendritic cells [10]. In addition, ATG therapy may facilitate tolerance induction through ATG-mediated apoptosis of T cells; because T cell apoptosis induced by anti-CD3 therapy was recently demonstrated to be associated with CD3 antibody therapy-induced immune tolerance [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggests that ATG therapy induces immune modulation beyond that of simple T cell depletion [9]. For example, ATG therapy may facilitate tolerance induction through modulation of dendritic cells (DC), both phenotypically and functionally [10]. Evidence has also shown that ATG therapy may also induce regulatory T cells (Tregs) in vivo [11-13].…”
Section: Introductionmentioning
confidence: 99%
“…Spleen and draining LN (left renal LN) were harvested to analyze CD4 ϩ CD25 ϩ FOXP3 ϩ regulatory T-cell populations by intracellular staining and flow cytometry. Splenocytes were analyzed for tumor necrosis factor-␣-and interferon-␥-producing T cells by intracellular staining and flow cytometry, as previously described (12).…”
Section: Islet Transplantationmentioning
confidence: 99%